Implementation of Problem-Based Learning Model in TOEFL Preparation Program at Khairun University - Sutisno Adam; Sulmi Magfirah (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
This study aimed to measure the effectiveness of the implementation of TOEFL Preparation in order to increase the students’ TOEFL test scores, then the scores can be used for academic purposes. The research conducted was an experimental study with a paired-sample t-test. Participants consisted of 20 selected students at Khairun University, namely through pretest, treatment (listening, structure, reading), and posttest. The research method used two types of instruments: pre-test, which used to measure the TOEFL test initial score, and post-test, which was used to measure the final score. The data collected from both the pre-test and post-test is then analyzed by using the paired-sample t-test in SPSS. The result showed that there were significant differences between students' scores in the pre-test and post-test in the three sections: Listening, Structure and written Expression, and Reading Comprehension. It also showed that the overall TOEFL preparation class students have increased scores. The part that has the biggest difference was the reading skill compared to the previous two sections. The students’ maximum score increased in the post-test in all three sections which means there was an increase of the score. The effectiveness of this program was strongly supported by the implemented learning model, namely PBL. The implementation of PBL in this program is very relevant because students are guided to identify the problems that usually arise in TOEFL questions and how to solve them.